Global research in schizophrenia and serotonin: a bibliometric analysis - Canul-Medina, Gustavo; López-Pech, Gael; Jiménez-Trejo, Francisco (Frontiers in Psychiatry, 2024)
Background: Schizophrenia is a chronic mental illness that affects millions of individuals worldwide. The etiological origin of schizophrenia is heterogeneous, but it has been shown to be associated with dysfunction in serotonin activity, serotonin receptors, and serotonin metabolism in the brain. Bibliometric analysis is a tool used to scrutinise and analyse research activities and evidence in a specific research area. No existing bibliometric analyses have considered both serotonin and schizophrenia.We conducted a bibliometric analysis including 12,027 studies related to the schizophrenia-serotonin link published from the inception of the study to 2023 and available in the Scopus database. We used VOSviewer software to identify global trends, analyse the author and editors keywords, the most cited articles and author, as well as the most productive institutes and journals publishing research on schizophrenia-serotonin link.Results: Most publications related to the link between schizophrenia and serotonin are focused on adult humans and examine topics such as antipsychotic agents, depression, and serotonin uptake inhibitors. The Journal of Clinical Psychiatry has published the most papers on the schizophrenia-serotonin relationship. Among nations, the United States is the leader in publications. King's College London is the institution with the highest number of publications, and H. Y. Meltzer is the most influential author. Growing trends in schizophrenia-serotonin research are personalised medicine, alternative medicine, transcranial magnetic stimulation, artificial intelligence, nervous system inflammation, brain-gut axis, and the gut microbiome.Since 1950, there have been several fluctuations in the number of published studies related to schizophrenia and serotonin. We believe that the development of novel medications and treatments for schizophrenia will be increased in the future, as well as research into genetic risks, psychological factors, and cranial neuroimaging components. Future schizophrenia and serotonin research is likely to focus on personalised medicine, alternative therapies, novel pathogenesis of schizophrenia, and the use of emerging technologies such as artificial intelligence.